2004
DOI: 10.1002/pri.296
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and beliefs of Brazilian and Australian physiotherapy students towards chronic back pain: a cross‐cultural comparison

Abstract: As demonstrated by higher HC-PAIR scores, the Brazilian physiotherapy students agree more strongly with the notion that low back pain justifies disability and activity limitation than do Australian physiotherapy students and North American healthcare providers. A history of chronic low back pain does not affect students' attitudes and beliefs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
57
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 20 publications
6
57
1
4
Order By: Relevance
“…This finding is consistent with a previous work by Nyland and Grimmer [32] that also found an increased lifetime prevalence of LBP in physiotherapy students and a significantly increased risk for students once they completed first year. However, previous research has not found association between health care providers personal experience of back pain and both the level of fear-avoidance beliefs [10,11,33] and the HC-PAIRS score [16,17].…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…This finding is consistent with a previous work by Nyland and Grimmer [32] that also found an increased lifetime prevalence of LBP in physiotherapy students and a significantly increased risk for students once they completed first year. However, previous research has not found association between health care providers personal experience of back pain and both the level of fear-avoidance beliefs [10,11,33] and the HC-PAIRS score [16,17].…”
Section: Discussionmentioning
confidence: 82%
“…In our study the average responses also were trended towards agreement (item 10: 4.77 and item 13: 4.36) but revealed good correlation with the tendency given in the other items. Some studies have found differences in how back pain is faced among different cultural backgrounds by patients [30] and by health care providers [15,16]. For example, Kovacs et al [18] demonstrated that in Spanish LBP patients the influence of fearavoidance beliefs is sparse in disability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only one study 27 evaluating attitudes and beliefs towards low back pain has been conducted in Brazil. The study by Ferreira et al 27 measured the attitudes and beliefs of 153 Brazilian physical therapy students, who had not yet taken the subject on low back pain and compared the results to those of 618 Australian physical therapy students. Students' beliefs and attitudes were measured by the Health Care Providers' Pain and Impairment Relationship Scale (HC-PAIRS) 8 .…”
Section: Introductionmentioning
confidence: 99%